ANALISIS TINGKAT PENGUKURAN KEPUASAN KONSUMEN TERHADAP LAYANAN TRANSAKSI ONLINE MENGGUNAKAN METODE SERVICE QUALITY(SERVQUAL): STUDI KASUS MEAT YOU PANGKALPINANG - Parlia Romadiana,; Zaid Prayogi, (Juremi: Jurnal Riset Ekonomi, 2025)
Frozen food is a very promising business opportunity for anyone who wants to start a business, namely a business that operates in the field of selling cold food. Meat you as part of the processed food or ready-to-eat food industry, meat you sell various complete frozen food products such as meat, vegetables, fruit, and so on. This research aims to determine the level of consumer satisfaction with online services at Meat You Pangkalpinang by calculating the difference between reality/perception and expectations. The method used is service quality (servqual). The dimensions used are tangible, reliability, responsiveness, assurance, and empathy. Based on the results of the reality/perception and expectation validity test, the calculated r-value exceeds the table r, namely 0.2656, this shows that all the reality/perception and expectation questionnaire statement items are valid. The results of the reality/perception reliability test on the dimensions Tangible 0.795, Reliability 0.830, Responsiveness 0.903, Assurance 0.816, and Empathy 0.837. The reliability test of expectations on the dimensions Tangible 0.906, Reliability 0.871, Responsiveness 0.921, Assurance 0.860, and Empathy 0.903. This shows that this value is very high and exceeds the correlation value of 0.6 and is said to be reliable. The results of the servqual calculation show that consumer satisfaction at Meat You Pangkalpinang seen from the 5 servqual dimensions has an average expected value of 4.57 and an average reality/perception value of 4.56. From processing the Servqual calculation data, it shows that consumers feel that almost all of their expectations are fulfilled by the services provided by Meat You Pangkalpinang with 99.78%, including customers being satisfied with the admin's agility in dealing with consumer complaints, customers being satisfied with the consistency in the quality of the products provided by Meat. you Pangkalpinang, and customers are satisfied with the timeliness of product delivery. It can be concluded that this can make customers more loyal to online shopping and customers are satisfied with the online services provided by Meat You Pangkalpinang.